2010
DOI: 10.3109/01913121003644781
|View full text |Cite
|
Sign up to set email alerts
|

Chromatin Alterations in Leukocytes of First-episode Schizophrenic Patients

Abstract: Studies of peripheral blood leukocytes of schizophrenic patients have shown in electron microscopy (EM) that decondensation of the chromatin constitutes a biological marker indicating increased genomic expression. Since this increase depends on chromatin relaxation by dissociation of lysine-rich histone H1 from nucleosomes, with exposure of arginine residues of core histones, the ratio of arginine to lysine residues in each nucleus represents a reliable measure of activation. Lysine- and arginine-rich proteins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Small-sized 1q12 domains translocated to the central nucleus area; the nucleoli occupied a large area and approached the 1q12 region. SZ patients' lymphocytes activation has been repeatedly described in a number of papers (Hirata-Hibi et al, 1982;Kloukina-Pantazidou et al, 2010;Uranova et al, 2017). Some authors have described the nucleolus increase (Uranova et al, 2017).…”
Section: White Blood Cells Of Sz Patients Show a Response Comparable mentioning
confidence: 94%
“…Small-sized 1q12 domains translocated to the central nucleus area; the nucleoli occupied a large area and approached the 1q12 region. SZ patients' lymphocytes activation has been repeatedly described in a number of papers (Hirata-Hibi et al, 1982;Kloukina-Pantazidou et al, 2010;Uranova et al, 2017). Some authors have described the nucleolus increase (Uranova et al, 2017).…”
Section: White Blood Cells Of Sz Patients Show a Response Comparable mentioning
confidence: 94%
“…Measurements of H3K9ac revealed that schizophrenia subjects are less efficient in ‘opening up’ their chromatin given the same blood levels of the HDAC inhibitor valproic acid [5]. Another recent study has measured the extent of decondensation of the genome in PMBCs from living schizophrenia patients as measured by the level of exposed arginine residues in the core histones [48]. This investigation reports a higher ratio of arginines:lysines, indicating a more reactive genome in patients with a new onset of schizophrenia.…”
Section: Psychiatric Epigenetic Studies Using Peripheral Blood Chromamentioning
confidence: 99%